Prediction of hydraulic conductivity of fly ash built-in mineral sealing layers - Wasil, Mariola (International Conference “Environmental Engineering”, 2017)
Mineral barrier protects the groundwater and soil from contamination by insulating the leakage of harmful substances from landfill. One of the most important parameters, which decides about usefulness of material to built-in sealing layers, is hydraulic conductivity. Researchers have conducted investigations with the possibility of utilising fly ash as a mineral sealing layer material, which is justified by its low permeability and other properties. It is known that laboratory tests of hydraulic conductivity are often long-term and require expensive equipment. Therefore, to avoid this, researchers trying to assess permeability of tested material with empirical or semi empirical formulas. The aim of the paper is to compare the results of hydraulic conductivity of fly ash obtained from the laboratory tests and from estimation using different empirical formulas. Fly ash was compacted by the Standard Proctor compaction method at the optimum moisture content. The results obtained from empirical equations were variable. It was observed that the Kozeny-Carman formula and other, based on a few physical parameters of the soil, gave better results in prediction of hydraulic conductivity of fly ash than equations based on only one parameter.